Exploring the relationship between bearing extrusion and postoperative persistent pain in Oxford unicompartmental knee arthroplasty: A trajectory measurement study - Wen, Pengfei; Zhang, Qidong; Sun, Xiaowei; Zhang, Binfei; Ma, Tao; Zhang, Yumin (Frontiers in Bioengineering and Biotechnology, 2022)
Objective To explore the relationship between the extrusion of the meniscus bearing and postoperative persistent pain of Oxford unicompartmental knee arthroplasty. Methods Patients undertaken Oxford UKA from January 2019 to June 2020 were retrospectively analyzed. Intraoperatively, the displacement and the movement trajectory of the meniscus bearing was recorded by specially-designed gridding mould of tibial component. The k-means clustering analysis were applied based on the incidence of postoperative persistent knee pain and the bearing extrusion distance. The intraoperative meniscus bearing movement trajectories were analyzed between the two groups as well as the patients’ clinical outcomes and radiographic assessments. Results The k-means clustering analysis indicated that the extrusion of the bearing of 5mm was the grouping standard. There were 27 patients with 30 knees in the extrusion group and 58 patients with 68 knees in the non-extrusion group. The proportion of optimal bearing movement trajectories in the extrusion group was significantly lower than that in the non-extrusion group (P<0.05). The incidence of postoperative persistent knee pain in the extrusion group was higher than non-extrusion group (P<0.05). Radiographic assessment showed that the continuity of the femoral and tibial components in the extrusion group was greater than that in the non-extrusion group (P<0.05). However, there were no differences in pre- and postoperative HKAA, the varus/valgus degree of both femoral and tibial components, the flexion/extension angles of femoral component, and tibial slope also showed no statistical difference (P>0.05). Conclusion For Oxford mobile bearing UKA, the extrusion of meniscus bearing over 5mm may increase the incidence of postoperative persistent knee pain, while the improvement of bearing movement trajectory can effectively reduce this complication.